Inhibitory Effect of Mammea africana on Alpha-Amylase and Alpha-Glucosidase Enzymes of Rats - Nwakaego Omonigho Ebong; Jude Efiom Okokon; Jesse Idakwoji (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2022)
Mammea africana Sabine (Guttiferae), a medicinal plant used traditionally in the treatment of diseases including diabetes was evaluated for effect on alpha-amylase and alpha-glucosidase enzymes in vivo. The stembark extract (30, 60 and 90 mg/kg) of M. africana were investigated in vivo for inhibitory effect on alpha-amylase and alpha-glucosidase enzymes using starch, sucrose and maltose as substrates. Acarbose was used as reference drug. The stembark extract caused significant (p<0.05) reduction in blood glucose levels of treated rats with the various substrates used. The results suggest that the stembark extract of M. africana have the potentials to inhibit alpha-amylase and alpha-glucosidase in rats.